COMPARISON OF SHARIA AND CONVENTIONAL BANKING BANKRUPTCY RATES IN INDONESIA - Ulumuddin Nurul Fakhri; Saiful Anwar; Rifki Ismal; Ascarya . (Institute for Research and Community Empowerment (LPPM TAZKIA), 2019)
The purpose of this study is to determine the position of financial performance, the position of bankruptcy rates of Islamic banking, as well as compare it with conventional banking. This study also compares the accuracy of the bankruptcy predictions of the Islamic banks versus conventional banks using the Altman Z-Score method with the calculation of the financial services authority (OJK). This research will be very useful to provide early warning to Islamic banking in managing the company so that the company management can create some innovations in order to develop the company, avoid bankruptcy. The analysis of this research using some methods. First, the method of Approach Regulation of the Financial Services Authority no. No. 8 / POJK.03 / 2014 which refers to Central Bank of Indonesia regulation no. 9/1 / PBI / 2007 to know the position of financial performance. Second, the Altman Z-Score model to find out the bankruptcy positions of sharia and conventional banking. This study provides the finding of the position of the financial performance level and the position of bankruptcy level of sharia and conventional banking. The conclusion of this research is the performance of sharia banking is not better than conventional banking financial performance, because the position of Islamic banking performance level is ranked 3, while conventional banking is ranked 1. The risk of bankruptcy of sharia bank CBGB 2 is in the position of the gray zone, while conventional banking CBGB 2 is in the safe zone. These results prove that both Altman Z-Score method and the method of Approach Regulation of the Financial Services Authority can provide the same prediction result.